2012
DOI: 10.1007/s00296-011-2333-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of diffusion-weighted magnetic resonance imaging in early diagnosis of ankylosing spondylitis

Abstract: The objective of this study is to estimate the value of diffusion-weighted MRI (DWI) in the detection of abnormalities in sacroiliac joints in the patients with early ankylosing spondylitis (AS) and investigate the feasibility of whole-body DWI (WB-DWI) in systemic evaluation of AS. Sixteen patients with early AS, 18 patients with simple low back pain (LBP), and 18 healthy volunteers were involved in this study. All subjects underwent conventional MRI and DWI. Apparent diffusion coefficient (ADC) in subchondra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
4
13
0
1
Order By: Relevance
“…There are slight differences in the ADC values in different studies that may be attributed to the different MRI device and different b values. Moreover, similar to the studies of Gezmis et al 6 and Ai et al 15 and unlike the studies of Zhang et al 21 and Sanal et al, 16 the ADC values of unaffected portions of sacroiliac joints in patients with active sacroiliitis were also greater than the ADC values of bone marrow in patients with chronic back pain. This result may be due to the extensive spread of active lesions to the subchondral bone marrow area.…”
Section: Discussionsupporting
confidence: 33%
See 2 more Smart Citations
“…There are slight differences in the ADC values in different studies that may be attributed to the different MRI device and different b values. Moreover, similar to the studies of Gezmis et al 6 and Ai et al 15 and unlike the studies of Zhang et al 21 and Sanal et al, 16 the ADC values of unaffected portions of sacroiliac joints in patients with active sacroiliitis were also greater than the ADC values of bone marrow in patients with chronic back pain. This result may be due to the extensive spread of active lesions to the subchondral bone marrow area.…”
Section: Discussionsupporting
confidence: 33%
“…With the rapid progress of advanced imaging techniques, DWI and whole body-DWI will likely provide a widened application in the early diagnosis and long-term follow-up in AS patients. 15 Moreover, Sanal et al 2,16 performed two studies in 2013 with 21 and 33 patients and stated that DWI is comparable to visual analysis and active lesions in sacroiliitis of AS patients serving an adjunct to STIR. Also, they demonstrated that DWI may reflect the inflammatory state of disease by quantifying the bone marrow changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Several groups compared sacro-iliac lesions of SpA patients with normal appearing marrow of the same patients and found significantly higher ADC values in lesions then in normal-appearing bone marrow within the same patients. [33][34][35][36] Moreover, ADC is reported to be significantly higher in patients with active ankylosing spondylitis as compared with patients with chronic ankylosing spondylitis or clinically non-active disease. [35][36][37][38] Also, when comparing SpA patients with control patients without inflammatory back pain, higher ADC values were found in bone marrow of sacral and iliac bones of patients as compared with ADC values observed in controls.…”
Section: Dwi In Spondylarthropathymentioning
confidence: 99%
“…Attempts to diagnose marrow inflammation by DWI show some promise in the sacrum. 2 Although improved sensitivity with this sequence (even simply using the B0 image; ►Figs. 2B and 3B) may come at the expense of lower specificity, based on correlation with biopsy material, current MRI sequences are relatively insensitive for the detection of inflammation.…”
Section: Active Inflammationmentioning
confidence: 99%